PD-1 inhibitor combined with paclitaxel and cisplatin in the treatment of recurrent and metastatic hypopharyngeal/laryngeal squamous cell carcinoma: efficacy and survival outcomes - Fang, Qi; Li, Xiaodi; Xu, Pengfei; Cao, Fei; Wu, Di; Zhang, Xinrui; Chen, Chunyan; Gao, Jianming; Su, Yong; Liu, Xuekui (Frontiers in Immunology, 2024)
Objective: This retrospective study analyzed the efficacy of PD-1 inhibitors combined with albumin-bound paclitaxel and cisplatin (TP regimen) in the treatment of recurrent and metastatic hypopharyngeal/laryngeal squamous cell carcinoma (RMHSCC/RMLSCC). Methods: Patients diagnosed and treated at the Sun Yat-sen University Cancer Center from August 1, 2020, to August 15, 2023, with histologically confirmed RMHSCC/RMLSCC were included. All patients received PD-1 inhibitors combined with albumin-bound paclitaxel (260mg/m2) and cisplatin (60mg/m2) for 3-4 cycles. The primary endpoints were overall survival (OS) and progression-free survival (PFS). Results: A total of 50 patients with RMHSCC/RMLSCC who received TP+PD-1 inhibitor therapy were included, with an objective response rate (ORR) of 56.0% (28/50). The 1-year and 2-year OS rates were 80.2% (95% CI: 69.3%-92.9%) and 68.6% (95% CI: 52.6%-89.5%), respectively, while the 1-year and 2-year PFS rates were 44.7% (95% CI: 31.9%-62.5%) and 26.0% (95% CI: 12.6%-53.4%), respectively. Treatment-related adverse events mainly included rash, myelosuppression, gastrointestinal reactions, and hypothyroidism. Conclusion: In the treatment of RMHSCC/RMLSCC with TP + PD-1 inhibitors, survival rates of patients can be improved while ensuring the safety of the treatment regimen.